PEMBELAJARAN MUATAN LOKAL BAHASA JAWA DALAM PELAKSANAAN KURIKULUM 2013 DI SDN SAMBIROTO 01 SEMARANG (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2019)
The implementation of the 2013 curriculum in Elementary Schools is reflected in thematic-integrative learning. Some subjects are combined and integrated into the theme, except PJOK, Religious Education and Local Content. Learning local content aims to develop the local potential of the region through education. Local content subjects in Elementary Schools are developed in accordance with their respective regional policies. Regional languages ​​become local content set in Central Java. There are several obstacles in implementing Javanese language learning in elementary schools. One of the obstacles is students who begin to leave Javanese as a daily language. The implementation of learning is still not meaningful for students, it makes students increasingly not interested in learning Javanese. The various difficulties in learning the local content of Javanese language need to be overcome by various solutions and actions both in terms of learning, as well as government policies and adapted to the implementation of the 2013 curriculum that currently applies. Solutions to overcome these problems are in the hands of principals, teachers and students themselves.